Model‐based optimization of the feeding policy of a fluidized bed bioreactor for mercury uptake by immobilized Pseudomonas putida cells. Issue 5 (10th May 2016) - Şcoban, Andreea Georgiana; Maria, Gheorghe
Abstract: A model‐based analysis of a three‐phase continuously operated fluidized bed bioreactor is developed in order to determine the multi‐objective optimal feeding policy of the immobilized biomass used for removing mercury ions from wastewater. The analysis is focus on finding the optimal feeding policy of alginate porous beads of known particle size containing immobilized biomass ( Pseudomonas putida bacteria) to minimize the biomass consumption, while keeping a quasi‐constant high conversion. The extended bioreactor model is accounting for the biomass growth, biodegradation, and its partial leakage and washout. Bioreactor dynamics prediction has been generated by using a simple Michaelis–Menten kinetic model adopted from literature. The resulted optimal feeding policy of the bioreactor points out the importance of the adoption of an extended and adequate process/reactor model able to solve engineering operation problems by quickly adjusting the feeding conditions according to the time‐varying characteristics of the biomass culture and to the limited possibilities to control the process during the wastewater residence time in the bioreactor. © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.